Natural environment in The Black Heralds - Velázquez Rojas, Manuel (2019)
I will approach the analysis and exegesis of the denotative lexemes that correspond to the three natural spaces (animal, vegetable and mineral) that appear in the poems of The Black Heralds. Then I will enter the connotative depths of meaning expressed in the poems to reveal their structure and their indissoluble unity with its natural Andean reality (Santiago de Chuco) and coastal reality (Trujillo and Lima), demonstrating the deep natural root of Peruvianness in Vallejo’s poetic creation.